Stationary solutions to a degenerate logistic equation with superlinear or asymptotically linear nonlinearity - Furtado, Flávia Elisandra Magalhães (2024)
Tese (doutorado) — Universidade de Brasília, Instituto de Ciências Exatas, Departamento de Matemática, 2024.